Nutritional supplement habits: the survey on a Sicilian group - Macchiarella, Alessandra; Amato, Alessandra; Sacco, Alessia; Rabboni, Mirko; Contrò, Valentina; Proia, Patrizia (Akademia Wychowania Fizycznego w Poznaniu)
Dietary supplements are extensively used among athletes as well as amateurs attending gyms. Regardless of very poorly investigated information about the effects of these products– both desirable and adverse – a wide range of population is used to take them. The aim of this study was to investigate the supplement consumption in Sicilia, Italy. An online questionnaire has been administered to 588 subjects (55% male and 45% female) aged between 15 and 53 years, frequenters and non-frequenters of gyms. The questionnaire showed that 75%of subjects practice (more or less regularly) physical activity 3-4 times a week, whilst the 25% did not practice any sport. Saline Supplements (Gatorade, Powerade, etc.), Branched Amino Acids (BCAAs) and protein supplements were the most frequently indicated dietary supplements (25.2%, 19.4% and 27%); carnitine and creatine the least (6.8% and 11.6%). Most of the practicing sport respondents administer nutritional supplements by themselves and they do not acknowledge any noticeable performance improvement. Therefore, even if there is no definite posology for the use of supplements, these should never be considered as an alternative to foods and a proper lifestyle
Keywords: dietary supplements; Sicilian people; questionnaire